Online Learning in EFL Classroom during Pandemic COVID19 : Teaching Activities, Problems and Solutions - Sri Damayanti; Irwan Irwan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This study aims at finding out online teaching activities, online learning difficulties faced by EFL teachers and students, and students’ parents during the Covid-19 pandemic and solutions to solve them.  Some EFL lecturers volunteered to participate in this research through invitation. The EFL teachers were requested to make written reflections regarding their practices in carrying out online EFL learning and the challenges they encounter. Five of them were involved in a follow-up interview individually. Semi-structured interview was administered. Data coding was done and appropriate extracts were informed in results section. To validate the data, data coding was done independently by study. As results, the EFL teachers have carried out online learning through a series of activities ranging from checking the students’ attendance to giving score on the students’ works synchronously or asynchronously depending on each school policy. Various applications and platforms ranging from learning management system to additional resource are employed. However, many problems emerge from the students, the teachers, and the students’ parents along with the valid reasons. Therefore, the online learning does not run well since it lacks of preparation and planning. Implications for better online learning are discussed. Future prospective researches are directed and encouraged